ANALISIS PENERAPAN (SAK) 102 TENTANG PEMBIAYAAN MURABAHAH PADA KOPERASI JASA KEUANGAN SYARIAH (KJKS) IBU MANDIRI UNGARAN - Penta Widyartati; Sri Wiranti Setiyanti; Susanti Cahyaning Dwi Utami (Sekolah Tinggi Ilmu Ekonomi Semarang, 2023)
At this time the development of Islamic financial institutions is growing so rapidly. This can be seen from the many Islamic banks and other Islamic financial institutions such as Islamic Financial Services Cooperatives (KJKS). For the sake of transparency, accountability and comparability of sharia financial reports, it is necessary to have SAK syariah which regulates it, especially SAK 102, but there are still many KJKS that have not implemented it. The purpose of this study was to determine the suitability between the application of murabahah financing accounting with SAK 102 at KJKS Ibu Mandiri Ungaran. The informants in this study were managers and tellers at KJKS Ibu Mandiri. The research variables are murabahah financing at KJKS and SAK 102. Data collection methods are interviews and documentation to collect data about the application of murabahah financing accounting. Methods of data analysis using descriptive qualitative method. The results of the study show that KJKS has not fully implemented SAK 102. Because the recognition of receivables, calculation of fines, presentation and disclosure of murabahah financing is not in accordance with SAK 102. The advice given is KJKS Ibu Mandiri to carry out murabahah financing accounting in accordance with SAK 102 related to recognition, measurement, presentation and disclosure.